World Haptics 2009 - Third Joint EuroHaptics Conference and Symposium on Haptic Interfaces for Virtual Environment and Teleoper 2009
DOI: 10.1109/whc.2009.4810855
|View full text |Cite
|
Sign up to set email alerts
|

Wind display device for locomotion interface in a virtual environment

Abstract: This paper describes development of a wind display system for the TreadPort virtual environment locomotion interface, which is cumulatively known as the TreadPort Active Wind Tunnel (TPAWT).Computational Fluid Dynamic simulations and experiments with a scaled model test-bed of the system has resulted in a combination of passive and active controls capable of controlling wind speed and angle acting on a user in the environment. Development of the full scale TPAWT system is then described, which requires conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Previous studies on scaled system showed promising results [6][7][8][9]. Key features of the full-scale system adapted from scaled system and the major difficulties and features that required modifications are stated below.…”
Section: Major Modifications From Scaled Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on scaled system showed promising results [6][7][8][9]. Key features of the full-scale system adapted from scaled system and the major difficulties and features that required modifications are stated below.…”
Section: Major Modifications From Scaled Modelmentioning
confidence: 99%
“…Since the display screens are being used to guide the flow, an examination of the effect of wind loading due to dynamic pressure on the screens is essential. A finite element analysis of the pre-existing screens due to the addition of the wind tunnel, using ANSYS, estimated screen displacements of ~29 cm for the original constraints and 1.1 mm for thicker (1.9 cm) screens and modified constraints [8,12]. Experimental measurements using dial indicators measuring screen displacement for a range of steady operating fan frequencies on the fully built TPAWT system demonstrated that the pressure profiles on the screen and the resulting deflections are much lower-in a range of 0.2 to 2.5 mm with the existing screens, Table 4.…”
Section: Effect Of Wind On Display Screensmentioning
confidence: 99%
See 2 more Smart Citations
“…This system consists of the integration of the TreadPort locomotion interface (Hollerbach et al 2000) with a wind tunnel for atmospheric display (Kulkarni et al 2009(Kulkarni et al , 2012. The TreadPort is composed by a CAVE-like visual interface, as well as a harness and a treadmill that provide accurate locomotion forces as a user walks through a virtual environment.…”
Section: Virtual Realitymentioning
confidence: 99%